The Issue of Staff Training and Their Social Protection in the Field of Transport - Ishmurzayeva Dilorom Toshmirzayevna (Genius Journals, 2023)
The article deals issues with personnel training and their social protection in the field of transportation.
Keywords: Transport; automobile; magnetic field; air transport material